2011
DOI: 10.1016/j.jacc.2011.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amino-Terminal Pro–B-Type Natriuretic Peptide to Guide Outpatient Therapy of Patients With Chronic Left Ventricular Systolic Dysfunction

Abstract: In patients with HF due to LV systolic dysfunction, NT-proBNP-guided therapy was superior to SOC, with reduced event rates, improved quality of life, and favorable effects on cardiac remodeling. (Use of NT-proBNP Testing to Guide Heart Failure Therapy in the Outpatient Setting; NCT00351390).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
235
2
21

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 330 publications
(269 citation statements)
references
References 34 publications
7
235
2
21
Order By: Relevance
“…In some studies, a prespecified treatment escalation algorithm was followed21, 22 while in other studies the attending clinician was instructed to escalate treatment according to their individual clinical judgment 23, 24, 25. Our study used an empirical prespecified treatment escalation strategy that, included increasing existing doses of furosemide followed by introduction of thiazide diuretics and spironolactone, similar to the algorithms described in the aforementioned human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, a prespecified treatment escalation algorithm was followed21, 22 while in other studies the attending clinician was instructed to escalate treatment according to their individual clinical judgment 23, 24, 25. Our study used an empirical prespecified treatment escalation strategy that, included increasing existing doses of furosemide followed by introduction of thiazide diuretics and spironolactone, similar to the algorithms described in the aforementioned human studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a prospective study addressing the function of Nterminal pro-B-type natriuretic peptide (NT-proBNP) in guiding the treatment options for cases with impaired left ventricle (LV) systolic function, NT-proBNP-guided therapy was associated with lower event rates, improved living conditions, and superior LVEF (left ventricular ejection fraction) compared to standard therapies, independent on the age of the subjects (p = 0.03). 2 The Atherosclerosis Risk in Communities (ARIC) Study, recruiting 12,230 patients with a body mass index (BMI) of ≥18.5 kg/m 2 and no history of HF at baseline, followed-up their evolution for a median of 20.6 years, and showed that NT-proBNP represents a valuable biomarker that offers significant prognostic information regarding the risk of developing HF. 3 …”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Az elmúlt évtizedben számos, nagyon heterogén vizsgálat értékelte a natriureticus peptidek szerepét a króni-kus szívelégtelenség kezelésének irányításában [39,40,41,42,43,44,45,46,47,48]. Bár a legtöbb vizsgálat-ban az értékelt biomarker alkalmas volt a betegek és a betegség súlyosságának követésére, a vizsgálatok egy részében ez nem járt együtt a morbiditás és a mortalitás csökkenésével.…”
Section: A Natriureticus Peptidek Szerepe a Krónikus Szívelégtelenségunclassified